Current status and development prospects of the digital collection «Virtual Herbarium ALTB» - A. V. Vaganov; K. E. Medvedeva (Проблемы ботаники Южной Сибири и Монголии, 2020)
The paper presents the current state of affairs and prospects for the development of the digital collection«Virtual Herbarium ALTB», created in 2010. The effectiveness of solving tasks using the digital collection within theproject «Flora Altaica» has been analyzed. The most demanded directions of development in cooperation with the GlobalBiodiversity Information Facility (GBIF) are estimated. Arguments are given about the necessity of integration interaction between the three actors in the development of the digital collection «ALTB Virtual Herbarium» – the project «FloraAltaica», GBIF, and open data specifications (Darwin Core and GeoJSON).